DATA MINING DENGAN ALGORITMA APRIORI UNTUK PENENTUAN ATURAN ASOSIASI POLA PEMBELIAN PUPUK - Amrin Amrin (Paradigma, 2017)
In order to find out what fertilizer purchased by consumers, can be done with analytical techniques that is the analysis of consumer buying habits. Detection of fertilizers often purchased simultaneously is done using association rules. In this research will be used a priori algorithm for determining the rules of association of fertilizer purchases. From the results of the discussion and analysis of data can be concluded that with the application of a priori algorithm in determining the combination between itemsets with minimum support of 20% and minimum confidence 75% found 6 association rules, which has the highest value of support and confidence is if the consumer made a purchase transaction of fertilizer Organic and urea fertilizers simultaneously with the value of 60% support and 86% confidence value. Thus, if there are consumers buying organic fertilizers, then the possibility of consumers buying urea fertilizer is 86%.